ANESTHESIA MANAGEMENT IN MODIFIED PARK BENCH POSITION IN NEUROSURGERY : A CASE REPORT - Wanda, Aprilia; Suarjaya, I Putu Pramana; Widnyana, Made Gede; Sutawan, IB Krisna Jaya; Ryalino, Christopher (Universitas Pahlawan, 2024)
The modified park bench position enhances surgical exposure while minimizing brainstem manipulation but poses significant anesthetic challenges. This case report aimed to describe the author’s anesthesia management in a modified park bench position for neurosurgery. A 39-year-old woman presented with intermittent headaches, nausea, and vomiting for three months, alongside vision deterioration. She denied loss of consciousness, seizures, weight loss, or trauma. Examination revealed typical vital signs, neurological function, and musculoskeletal integrity. Supporting tests showed elevated SGOT levels and a primary malignant brain tumor with suspected hemorrhage and surrounding vasogenic edema. She underwent craniotomy after fasting and standard anesthesia preparation. An arterial line, premedication, and intubation were administered, followed by five-hour surgery in the modified park bench position. Postoperatively, pain was managed with fentanyl, paracetamol, and ibuprofen. She was monitored in the ICU for seven days and discharged on the eighth postoperative day. In summary, managing primary malignant brain tumors like glioblastoma requires thorough preoperative assessment, precise anesthesia planning, and vigilant intraoperative monitoring for patient safety and successful outcomes. The collaborative effort of neurosurgery and anesthesia teams and postoperative care is vital for patient recovery and underscores the importance of comprehensive perioperative management.